The Effect Of Profitability, Leverage And Accounting Contributions On The Disclosure Of Sustainability Reports In Mining Companies Listed On The Indonesia Stock Exchange For The 2020-2022 Period - Maliska, Tasya; Wiyodo, Slamet (Utami Publisher, 2024)
This research was conducted with the aim of knowing the effect of Profitability, Leverage, and Liquidity on the disclosure of Sustainability Reporting in mining companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sample selection method used in this study was purposive sampling in order to obtain a sample of 35 companies that met the criteria. The analysis technique used in this research is multiple linear regression analysis technique. The results in this study indicate that Profitability has a positive effect on the disclosure of Sustainability Reporting in Mining companies listed on the Indonesia Stock Exchange for the 2020-2022 period, while Leverage and Liquidity have no effect on the disclosure of Sustainability Reporting in Mining companies listed on the Indonesia Stock Exchange for the 2020-2022 period.